2000
DOI: 10.21825/sg.v65i0.815
|View full text |Cite
|
Sign up to set email alerts
|

Aboveground biomass of Pinus halepensis Mill. forests in the Kassandra Peninsula - Chalkidiki

Abstract: Pinus halepensis occupies a large area of Mediterranean coastal forests. Kassandra Peninsula Pinus halepensis forests could be characterized as. the representative forests in the Mediterranean. These forests are very important, due to their vicinity to urban and coastal areas. The knowledge of biomass distribution in these forests will help with the correct time and space planning, in order to fulfil the multifunctional management of ecosystems (wood production, water, forest protection, recreation etc.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
(2 reference statements)
0
5
0
1
Order By: Relevance
“…The selected papers fulfilled the following criteria: (i) the study was published in English language; (ii) the scope of the study was biomass production in Aleppo pine stands. Smiris et al (2000) showed that the determination of the biomass distribution in Aleppo pine stands is important for their effective management, and for planning conservation strategies and ecosystem valorisation as well. Allometric models help estimate biomass or volumes based on the dendrometric parameters of sample trees (López-Serrano et al 2005, Ruiz-Peinado et al 2011).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The selected papers fulfilled the following criteria: (i) the study was published in English language; (ii) the scope of the study was biomass production in Aleppo pine stands. Smiris et al (2000) showed that the determination of the biomass distribution in Aleppo pine stands is important for their effective management, and for planning conservation strategies and ecosystem valorisation as well. Allometric models help estimate biomass or volumes based on the dendrometric parameters of sample trees (López-Serrano et al 2005, Ruiz-Peinado et al 2011).…”
Section: Methodsmentioning
confidence: 99%
“…1 summarizes the biomass models used in Greece and Spain for Aleppo pine. According to Smiris et al (2000), young (23-year-old) Aleppo pine stands have a productivity of 17.55 t ha -1 of biomass, which becomes 764.86 t ha -1 at the age of 48 years, 1192.24 t ha -1 at the age of 70 years, and finally 1406.21 t ha -1 at the age of 100 years. In this context, López-Serrano et al (2005) showed that biomass production varies significantly with age and environmental conditions.…”
Section: Iforest -Biogeosciences and Forestrymentioning
confidence: 99%
“…The above measurements were used in allometric equations developed for vegetation types similar to the ones observed in the study area [53][54][55][56][57] to obtain an estimate of the fuel load present on each plot, split into diameter categories as required for the description of fuel models. Based on the fuel estimates and the morphological characteristics of each vegetation type, a fuel model (FM) was assigned to each plot.…”
Section: Fire Behavior Simulation and Estimation Of Fire Hazardmentioning
confidence: 99%
“…Arianoutsou and Radea (2000) estimate that Aleppo pine species offers a significant amount of energy annually, based on the fact that approximately 0.17 kgm/m 2 of litter, analogous to 816 Kcal (1 Kg litter equals 4800 Kcal (MCFADYEN, 1971)) is produced annually by Aleppo pines, and the litter of the understorey shrubs add about 773 Kcal of energy to the subsoil. Removal of needles and thin branches frequently, although it reduces the possibility of fire, is not recommended, given that forest floor represents up to 50% of the total biomass and contains a great number of nutrients (ALIFRAGIS et al, 2001;SMIRIS et al, 2000). As expected, biomass production depends on the site; in good quality sites more biomass is found (SMIRIS et al, 1998); consequently, more energy is restored.…”
Section: Introductionmentioning
confidence: 99%